Model Law on Elderly Care Business - Permsin, Anuratch; Saowakon, Siwanporn; Usathaporn, Suthee (Interdisciplinary Academic and Research Journal, 2024)
Background and Aims: Providing care services for the elderly in service facilities Operators provide housing and care services to elderly people staying in such facilities. Some facilities only provide personal care services. The model for providing care for the elderly therefore needs to be clearly specified in detail beyond just specifying the format for providing care for the elderly in facilities and providing care for the elderly at home. Thus, the research on the model law on elderly care business aims to (1) investigate concepts, theories, and principles related to the nursing home business; (2) explore the legal measures of Thailand and foreign countries on nursing home business; (3) analyze the nursing home business; and (4) draft the model law on nursing home business. Methodology: This research applied a qualitative research methodology consisting of documentary research, in-depth interviews, and focus group discussions. Results: The results revealed that regarding the use of theories, principles, and concepts in analyzing nursing home business, specified the Health Establishment Act B.E.2559, the Ministerial Regulation specified healthcare business for elderly or dependent persons as other enterprises in health establishment B.E.2563, and the regulations of Department of Older Persons do not legislate a specific law to control nursing home business. Therefore, this kind of business lacks the criteria to control the standard of people performing the duties in taking care of and nursing older persons, to follow up a nursing home business, and to have no specific agencies to follow up a nursing home business. This causes the business to be conducted freely without keeping an eye on the performance, which is a gap for unlawful acts among some entrepreneurs and leads to physical damage or death of older persons. Moreover, older persons’ families must lose a large amount of income but do not get quality and standardized nursing as specified in the contract. Conclusion: According to the conclusion of this research, the researcher would like to propose the model law on nursing home business, that is, the draft act for nursing home business B.E. … consisting of (1) definition, (2) Section 1: Qualifications of Nursing Home Entrepreneurs, (3) Section 2: Registration and Licensing, (4) Section 3: Duties of Licensee, Manager, and Service Provider on Nursing Older Persons, (5) Section 4: Committees to Control Nursing Home Entrepreneurs, and (6) Section 5: Punishment.